2013
DOI: 10.1093/gbe/evt020
|View full text |Cite
|
Sign up to set email alerts
|

Number Variation of High Stability Regions Is Correlated with Gene Functions

Abstract: Various regulatory elements in messenger RNAs (mRNAs) carrying the secondary structure play important roles in a wide range of expression processes. Numerous recent works have focused on the discovery of these functional elements that contain the conserved mRNA structures. However, to date, regions with high structural stability have been largely overlooked. In this study, we defined high stability regions (HSRs) in the coding sequences (CDSs) in bacteria based on the normalized folding free energy. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…We calculated the ratio paired/unpaired and surprisingly found that the ratio is lower than the expected value in the two species ( t -test, all p- values <10 −7 , Table 3), which is different from the pattern inferred from the conserved secondary structure (the ratio is higher than the expected value) [27]. This result is consistent with the idea that structural stability instead of structural conformation in HSR is conserved during evolution [16], [35].…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…We calculated the ratio paired/unpaired and surprisingly found that the ratio is lower than the expected value in the two species ( t -test, all p- values <10 −7 , Table 3), which is different from the pattern inferred from the conserved secondary structure (the ratio is higher than the expected value) [27]. This result is consistent with the idea that structural stability instead of structural conformation in HSR is conserved during evolution [16], [35].…”
Section: Resultssupporting
confidence: 53%
“…We thus identified HSRs on mRNAs only based on the minimum folding free energy (MFE) of local regions. The method was described previously [16]. The main steps are as follows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonuniformity in the elongation step of translation could influence the fate of the newly synthesized polypeptide, including its subcellular localization, folding, modification, and stability (Zhang and Ignatova 2011;Pechmann and Frydman 2013;Kramer et al 2009;Zhou et al 2013). The rhythm in translation (Rosenblum et al 2013) is determined in part by features of mRNA, such as biased codon usage (Sorensen et al 1989;Plotkin and Kudla 2011), local secondary structure (Tholstrup et al 2012;Mao et al 2013), and complementary interactions with the RNA component of the ribosome (Li et al 2012). Can such mRNAinstructed translation modulation respond to environmental changes?…”
mentioning
confidence: 99%